Breaking the Forest Commons'Dilemma in the Philippines Creating an Annual Stream of Benefits as Incentive to Cooperation - Sebastian, Florencia Charito I. (2010)
This study is an auto-ethnographic research on Community Based Forestry Management (CBFM) program of the government. The author led the formation of people's organization (PO) in order to find out whether forest as knowledge-poor dwellers around the upland forest as beneficiaries would succeed. The author's case study is a mirror of the national experience of the program involving over one million hectares of forest land. The study presents the internal workings and difficulties encountered by a poor, incipient community that was heavily dependent on external assistance coming in trickles and over protracted time intervals. The first decade of devolution and partnership of government and non- government organizations (NGOs) in people's forestry in the 1990s serves as the backdrop of the CBFM. The study concludes that intermittent, project-supported community forest management with little local government intervention in the effort would not solve the dilemma of deforestation in the country.
Keywords: Community forest management